2010
DOI: 10.1021/nn100592d
|View full text |Cite
|
Sign up to set email alerts
|

Facile Coating of Manganese Oxide on Tin Oxide Nanowires with High-Performance Capacitive Behavior

Abstract: In this paper, a very simple solution-based method is employed to coat amorphous MnO2 onto crystalline SnO2 nanowires grown on stainless steel substrate, which utilizes the better electronic conductivity of SnO2 nanowires as the supporting backbone to deposit MnO2 for supercapacitor electrodes. Cyclic voltammetry (CV) and galvanostatic charge/discharge methods have been carried out to study the capacitive properties of the SnO2/MnO2 composites. A specific capacitance (based on MnO2) as high as 637 F g(-1) is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
357
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(371 citation statements)
references
References 39 publications
10
357
4
Order By: Relevance
“…Electrochemical analysis 4.1. Figure 1a shows the plot of capacitive performances for PACN composites at different scan rates (5,10,20,30,50,60,80 and 100 mV/s) in a threeelectrode configuration with applied potential. The capacitive performance was characterized by cyclic voltammetry (CV) in 1 (M) KCl solution to obtain the value of specific capacitance (C sp ) of the composites.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…Electrochemical analysis 4.1. Figure 1a shows the plot of capacitive performances for PACN composites at different scan rates (5,10,20,30,50,60,80 and 100 mV/s) in a threeelectrode configuration with applied potential. The capacitive performance was characterized by cyclic voltammetry (CV) in 1 (M) KCl solution to obtain the value of specific capacitance (C sp ) of the composites.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…However, in our case it was found that the electrolyte did slightly discolour after 2000 cycles. This indicates the dissolution of the MnO2 to soluble Mn 2+ at low potentials, which is a main cause of capacitance loss in MnO2-based supercapacitors 43 . This may suggest that CMHS and MHS are less stable than other forms of MnO2 at low potentials (a possibility we are currently investigating).…”
mentioning
confidence: 96%
“…This brings forth the search for a wide variety of materials. In general, transition metal oxides, including RuO 2 , MnO 2 , NiO, Co 3 O 4 , SnO 2 , ZnO, TiO 2 , V 2 O 5 , CuO, Fe 2 O 3 , and WO 3 (Lang et al 2011;Athoue et al 2008;Yan et al 2010;Chen et al 2012;Luo et al 2014;Liu et al 2014;Sathiya et al 2011;David et al 2014;Brezesinski et al 2009;Wang et al 2013;Liang et al 2010;Xia et al 2014;Kang et al 2013;Yu et al 2014), etc., have demonstrated high specific capacitance values with their redox reaction behaviors.…”
Section: Introductionmentioning
confidence: 99%